Performance Assessment in Strength and Conditioning - Comfort, Paul (Routledge, 2018)
It is an essential skill for any strength and conditioning coach to be able to reliably assess the physical performance of their athletes and communicate the results and their implications to performers and coaches, alike. Performance Assessment in Strength and Conditioning is the first textbook to clearly and coherently suggest the most appropriate and reliable methods for assessing and monitoring athletes' performance, as well as including detailed sections on testing considerations and the interpretation and application of results. The book explores the full range of considerations required to reliably assess performance, including questions of ethics and safety, reliability and validity, and standardised testing, before going on to recommend (through a comparison of field- and laboratory-based techniques) the optimal methods for testing all aspects of physical performance, including: injury risk jump performance sprint performance change of direction and agility strength power aerobic performance body composition Closing with a section on interpreting, presenting and applying results to practice, and illustrated with real-life case study data throughout, Performance Assessment in Strength and Conditioning offers the most useful guide to monitoring athlete performance available. It is an essential text for upper-level strength and conditioning students and practitioners alike